Ecotropic viral integration site 1, a novel oncogene in prostate cancer - Queisser, Angela; Duensing, Stefan (Oncogene, 2017)
Prostate cancer (PCa) is the most commonly diagnosed non-cutaneous cancer in men in the western world. Mutations in tumor suppressor genes and in oncogenes are important for PCa progression, whereas the role of stem cell proteins in prostate carcinogenesis is insufficiently examined. This study investigates the role of the transcriptional regulator Ecotropic Viral Integration site 1 (EVI1), known as an essential modulator of hematopoietic and leukemic stem cell biology, in prostate carcinogenesis. We show that in healthy prostatic tissue, EVI1 expression is confined to the prostate stem cell compartment located at the basal layer, as identified by the stem cell marker CD44. Instead, in a PCa progression cohort comprising 219 samples from patients with primary PCa, lymph node and distant metastases, EVI1 protein was heterogeneously distributed within samples and high expression is associated with tumor progression (P<0.001), suggesting EVI1 induction as a driver event. Functionally, short hairpin RNA-mediated knockdown of EVI1 inhibited proliferation, cell cycle progression, migratory capacity and anchorage-independent growth of human PCa cells, while enhancing their apoptosis sensitivity. Interestingly, modulation of EVI1 expression also strongly regulated stem cell properties (including expression of the stem cell marker SOX2) and in vivo tumor initiation capacity. Further emphasizing a functional correlation between EVI1 induction and tumor progression, upregulation of EVI1 expression was noted in experimentally derived docetaxel-resistant PCa cells. Importantly, knockdown of EVI1 in these cells restored sensitivity to docetaxel, in part by downregulating anti-apoptotic BCL2. Together, these data indicate EVI1 as a novel molecular regulator of PCa progression and therapy resistance that may control prostate carcinogenesis at the stem cell level.